Developing Science Teaching Book with a Scientific Approach to Analyze the Concept of Energy in the 7th Grade Junior High School - Agung Mulyo Setiawan; Savira Mahdia; Sugiyanto Sugiyanto (Journal of Disruptive Learning Innovation (JODLI), 2020)
The observation in the Junior High Schools (SMP/MTs) in Malang City found that students had difficulties in understanding energy in the life system’s topic. It is because learning is centered on the teacher, and the students only accept concepts explained by the teacher. Therefore, a science teaching book is needed to support student understanding of the energy in the life system’s material and the student-centered learning achieved. This study aims to produce a science teaching book with a scientific approach to analyze the concept of energy for seventh-grade junior high school that is valid and suitable for use in learning. The feasibility test is done through media validation, material validation, and limited readability tests. Media and material validation were carried out by one science education lecturer, and limited readability testing was carried out by three junior high school teachers and ten seventh grade junior high school students who had taken energy topic in the life system. The results of the study showed that the science teaching book with a scientific approach developed is valid and appropriate to use in the future.